Agama dan Sains: Sebuah Kajian Tentang Relasi dan Metodologi - Syarif Hidayatullah (Jurnal Filsafat "WISDOM", 2019)
The article aims to understand two issues related to sciences and religions. Firstly, in what forms are sciences and religions related? Secondly, how are the methods of that relation? For that purpose, the subject matter of this study are issues included in the relation between sciences and religion, especially those related to forms of relation and its methodological aspects, which will be discussed by proposing thoughts by a numbers of scholars with different background, especially from Christian-West and Muslims. In addtion, to respond to the research questions, the auhtor will employ Philosophy of Science as a perspective which simultanously be the formal object of the study. The study reveals that while sciences and religions are two difference entities as source of  knowledge and source of value of human, the relationship between the two is very dynamic. The dynamic involves conflicts and contrast, independent, dialogous and inter conversation and complatible, to the point of confirmation, integration and harmony.   Scientific method is applied by sceintists with particular ways of gaining knowledge about nature. However, when compared to method of knowledge included in religion, beside unique difference embedded in religion’s method, it can not be denied that there is similarity between the two, namely in relation to experience and intepretation, the role of community, analogue and models.